Interactive learning aided by JavaScript - A. Wise (Association for Learning Technology, 1999)
In recent years, the use of information technology to support learning in nutrition education has moved from mainframe-based programs to PC and Internet-based systems (Wise, 1986,1998). Many lecturers are now exploring the use of the Internet and Intranets for education and this adds a new potential method for providing support to students. A search of the Internet for a technical term frequently links to pages containing notes for students. Some of these pages contain interactive elements that test whether students have learned the material. This paper is a case study that attempts to show how simple it is to build interactivity for students using JavaScript. Many programs can be written using the language Java, but the browser needs to be specially configured and considerable programming experience is required. Java is frequently confused with JavaScript, which is actually a language supported entirely within the browser itself. A browser will interpret code in JavaScript that is simply included within appropriate HTML tags on the page. JavaScript is used to provide simple interactivity and most people will have spotted its common features: buttons and text entry used on forms to provide feedback to the originators of Web pages. An advantage of JavaScript is that browsers are able to use this language, whatever the operating system, not only in Windows.